Jintiange Capsules Ameliorate Osteoarthritis by Modulating Subchondral Bone Remodeling and Protecting Cartilage Against Degradation - Zhuang, Chenyang; Wang, Zixiang; Chen, Weisin; Wang, Hanquan; Tian, Bo; Lin, Hong (Frontiers in Pharmacology, 2021)
Osteoarthritis (OA) is the most prevalent joint disease worldwide, making it a major cause of pain and disability. Identified as a chronic and progressive disease, effective treatment at the early stages of OA has become critical to its management. Jintiange (Jtg) capsules are a traditional Chinese medicine produced from multiple organic components of various animal bones and routinely used to treat osteoporosis in China. However, the effect of Jtg on subchondral bone and cartilage degeneration in OA remains unknown. The purpose of the present study was to investigate the biomolecular role and underlying mechanisms of Jtg in OA progression. Herein, we found that Jtg inhibited receptor activator of nuclear factor-κB ligand (RANKL)-induced osteoclast formation and it functions through the NF-κB signaling pathway. Jtg also inhibited chondrocyte apoptosis via reducing the reactive oxygen species (ROS) concentration in these cells. Moreover, in vivo evaluation revealed that Jtg significantly attenuates subchondral bone remodeling and cartilage destruction in anterior cruciate ligament transection (ACLT) mouse models. Taken together, our data demonstrate that Jtg inhibits osteoclast differentiation in subchondral bone and chondrocyte apoptosis in cartilage, supporting its potential therapeutic value for treating OA.